Female Agripreneurs' Strategies for Coping with Climate-Driven Food System Disruptions - Tshikororo, Mpho (Economics and Entrepreneurship: The Proceedings of the 10\(^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Climate change continues to disrupt food systems around the globe. Climate change adaptation efforts for enhanced food production and quality contribute to increased production costs. The study sought to investigate the coping mechanisms that significantly contribute towards the sustainability of female agripreneurs in a dire situation brought by the discrepancies within the food systems synergy due to climate change. The study was conducted in the Thulamela local municipality in the Limpopo Province. Structured questionnaires were handed to 173 study participants during the in-person interview sessions, who were selected using the purposive sampling technique. A Binary Logistic Regression model was used to determine the observed discrepancies within the food production system caused by climate change. The Binary Logistic Regression model was used for its strength to provide a precise understanding of the relationship between business ownership, which is dichotomous and observed climate change discrepancies, which propelled the development of coping mechanisms. The study used three coping mechanism approaches related to the agribusiness's scope: industry, commerce, and trade. The study findings also indicated that female agripreneurs prioritized indigenous crops to minimize the cost of production while integrating traditional climate change strategies for other commodities. Within the commerce segment, new marketing initiatives, such as using marketing influencers and home delivery, enhanced customer recruitment and retention in the absence of marketing contracts. The study recommends the regulation of agricultural markets at a regional level to minimize market price volatility.